“You must learn to know me by that name” : Case Studies of Representation of Biblical People and Events in C. S. Lewis’ The Chronicles of Narnia - Liljeroos, Laura (My University, 2021)
In this thesis, I examine cases of intertextuality between C. S. Lewis’ The Chronicles of Narnia series and the Bible. The analysis consists of eight different case studies and it is constructed on two different levels; the first part focuses on the parallels between some characters of The Chronicles of Narnia and the people in the Bible, while the second part compares storylines and narratives in The Chronicles of Narnia to the relevant events, narratives and themes in the Bible. The findings are then critically scrutinised in light of the most prominent theories of intertextuality and intertextuality studies. In addition to the two primary sources, The Chronicles of Narnia and the Bible, the study also utilises a considerable body of other academic research on intertextuality, the Bible and The Chronicles of Narnia. Both levels of analysis demonstrate a considerable number of intertextual references to the Bible in The Chronicles of Narnia series. These references are spread across the seven volumes of the series and they are very extensive and detailed in nature. As C. S. Lewis was a devout evangelical Christian, the authorial design and intentionality of these references is likely. However, with the recent developments in the field of intertextuality studies, the focus has shifted onto the reader’s perception of intertextuality and its influence on their reading experience. In the case of The Chronicles of Narnia and the Bible, the intertextuality is supported by textual evidence, (assumed) authorial design and reader perceptions alike, justifying its obligatory classification. However, further research is needed on the practical dimension of intertextuality studies.
Keywords: The Bible, The Chronicles of Narnia, C.S. Lewis, intertextuality